Tumoricidal stem cell therapy enables killing in novel hybrid models of heterogeneous glioblastoma. Issue 12 (17th August 2019) - Satterlee, Andrew B; Dunn, Denise E; Lo, Donald C; Khagi, Simon; Hingtgen, Shawn
Abstract: Background: Tumor-homing tumoricidal neural stem cell (tNSC) therapy is a promising new strategy that recently entered human patient testing for glioblastoma (GBM). Developing strategies for tNSC therapy to overcome intratumoral heterogeneity, variable cancer cell invasiveness, and differential drug response of GBM will be essential for efficacious treatment response in the clinical setting. The aim of this study was to create novel hybrid tumor models and investigate the impact of GBM heterogeneity on tNSC therapies. Methods: We used organotypic brain slice explants and distinct human GBM cell types to generate heterogeneous models ex vivo and in vivo. We then tested the efficacy of mono- and combination therapy with primary NSCs and fibroblast-derived human induced neural stem cells (iNSCs) engineered with tumor necrosis factor–related apoptosis-inducing ligand (TRAIL) or enzyme-prodrug therapy. Results: Optical imaging, molecular assays, and immunohistochemistry revealed that the hybrid models recapitulated key aspects of patient GBM, including heterogeneity in TRAIL sensitivity, proliferation, migration patterns, hypoxia, blood vessel structure, cancer stem cell populations, and immune infiltration. To explore the impact of heterogeneity on tNSC therapy, testing in multiple in vivo models showed that tNSC-TRAIL therapy potently inhibited tumor growth and significantly increased survival across all paradigms. Patterns of tumor recurrence varied with therapeutic (tNSC-TRAIL and/or tNSC–thymidine kinase), dose, and route of administration. Conclusions: These studies report new hybrid models that accurately capture key aspects of GBM heterogeneity which markedly impact treatment response while demonstrating the ability of tNSC mono- and combination therapy to overcome certain aspects of heterogeneity for robust tumor kill.